A versatile genomic transgenesis platform with enhanced λ integrase for human Expi293F cells - Siddiqui, Asim Azhar; Peter, Sabrina; Ngoh, Eve Zi Xian; Wang, Cheng-I.; Ng, Shirelle; Dangerfield, John A.; Gunzburg, Walter H.; Dröge, Peter; Makhija, Harshyaa (Frontiers in Bioengineering and Biotechnology, 2023)
Reliable cell-based platforms to test and/or produce biologics in a sustainable manner are important for the biotech industry. Utilizing enhanced λ integrase, a sequence-specific DNA recombinase, we developed a novel transgenesis platform involving a fully characterized single genomic locus as an artificial landing pad for transgene insertion in human Expi293F cells. Importantly, transgene instability and variation in expression were not observed in the absence of selection pressure, thus enabling reliable long-term biotherapeutics testing or production. The artificial landing pad for λ integrase can be targeted with multi-transgene constructs and offers future modularity involving additional genome manipulation tools to generate sequential or nearly seamless insertions. We demonstrated broad utility with expression constructs for anti PD-1 monoclonal antibodies and showed that the orientation of heavy and light chain transcription units profoundly affected antibody expression levels. In addition, we demonstrated encapsulation of our PD-1 platform cells into bio-compatible mini-bioreactors and the continued secretion of antibodies, thus providing a basis for future cell-based applications for more effective and affordable therapies.